Solid-liquid mixed packaged perovskite quantum dot and preparation method thereof

Through solid-liquid hybrid packaging technology, organic ligands are used to passivate the surface defects of perovskite quantum dots and form a stearate coating layer on the outer layer, solving the problems of stability and luminous efficiency of perovskite quantum dots in high temperature and high humidity and light environments, and achieving a significant improvement in PLQY and light stability.

CN119875618AInactive Publication Date: 2025-04-25WENZHOU XINXIN TAIJING TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510062966.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the fluorescent quantum yield (PLQY) and stability of perovskite quantum dots, especially in high temperature and high humidity and light environments.

Method used

Solid-liquid hybrid packaging technology is used to passivate the surface defects of perovskite quantum dots through organic ligands, and a stearate coating is formed on the outer layer to enhance its stability.

Benefits of technology

The PLQY and light stability of perovskite quantum dots are significantly improved, allowing them to exhibit higher stability and luminous efficiency in high temperature and high humidity and light environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875618A_ABST
    Figure CN119875618A_ABST
Patent Text Reader

Abstract

The invention provides a solid-liquid mixed packaged perovskite quantum dot, which comprises a template agent with a pore channel, the pore channel of the template agent is internally provided with a perovskite quantum dot and an organic ligand, and the organic ligand is used for passivating surface defects of the perovskite quantum dot; the template agent further comprises stearate, the powder particle size of the stearate is larger than the pore diameter of the pore channels of the template agent, and the stearate deforms under the action of external force and then is partially embedded into the pore channels of the template agent to block the pore channels. According to the invention, the PLQY is improved by passivating uncoordinated lead on the surface of the perovskite quantum dot through an organic ligand, and then a coating layer is added on the outer layer of the perovskite quantum dot through a solid-state packaging technology, so that the perovskite quantum dot can better exist in a high-temperature and high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of post-processing of perovskite quantum dots, and in particular relates to a solid-liquid hybrid packaged perovskite quantum dot and a preparation method thereof. Background Art

[0002] As a new type of luminescent material, metal halide perovskite (hereinafter referred to as perovskite) luminophore has the characteristics of excellent luminescence efficiency, narrow emission half-peak width, high color purity, adjustable visible light band, etc., and is simple to prepare, low cost, and easy to scale up production. It is expected to become a key luminescent layer material in the future display field and has broad application prospects in light-emitting diodes (LEDs), solar cells, lasers and other fields. However, since perovskite is a soft lattice ionic compound, high humidity, high temperature and strong light irradiation in the external environment can easily induce perovskite defects, thereby damaging its luminescence performance. Therefore, perovskite needs to meet the tests of water, oxygen stability and light stability at the same time.

[0003] In order to further improve the PLQY and stability of perovskite quantum dots, it is a more feasible approach to effectively passivate and encapsulate perovskite quantum dots. At present, the synthesis of perovskite quantum dots usually uses Lewis base organics such as oleic acid, oleylamine, and phenylethylamine iodide to passivate the uncoordinated lead on the surface of the perovskite, so as to passivate the surface defects of the perovskite to improve the PLQY and stability of the perovskite quantum dots. However, such organics are easy to fall off in high temperature and high humidity environments and lose the passivation effect.

[0004] In order to encapsulate perovskite quantum dots, the existing technology also uses a high-temperature solid-state synthesis method, which is mainly divided into two steps: 1) mixing the perovskite precursor and the template; 2) calcining the precursor mixture, reacting and melting the perovskite precursor at high temperature, and supercooling and crystallizing in the template to form a perovskite luminescent body. Due to the coating effect of the template, these perovskite luminescent bodies can isolate water, oxygen and external high temperature, showing stability against water and high temperature.

[0005] However, the template only has a coating effect and cannot effectively passivate the perovskite luminescent body. Therefore, the perovskite luminescent body still has a large number of surface defects. These defects will cause the fluorescence intensity of the perovskite luminescent body to decrease in a high temperature or light environment. If the surface defects of the perovskite luminescent body are passivated in the template pores, it is necessary to retain the pores used as the post-processing mass transfer path (see the Chinese patent CN 118978913A previously applied by our company). However, the retention of the pores makes the template unable to completely block water and oxygen, so that water and oxygen stability and light stability cannot be taken into account at the same time. Therefore, it is urgent to develop a stable surface organic ligand passivation and encapsulation technology for perovskite quantum dots. Summary of the invention

[0006] The purpose of the present invention is to provide a solid-liquid hybrid encapsulated perovskite quantum dot and a preparation method thereof, wherein the uncoordinated lead on the surface of the perovskite quantum dot is passivated by an organic ligand to improve the PLQY, and then a coating layer is added to the outer layer of the perovskite quantum dot by solid-state encapsulation technology, so that it can better exist in a high temperature and high humidity environment.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A solid-liquid hybrid encapsulated perovskite quantum dot comprises a template having pores, wherein the pores of the template are provided with perovskite quantum dots and organic ligands, wherein the organic ligands are used to passivate surface defects of the perovskite quantum dots;

[0009] Also included is a stearate, which is deformed under the action of an external force and then partially embedded in the pores of the template to block the pores;

[0010] The particle size of the stearate powder>the pore size of the template>the size of the organic ligand molecule.

[0011] In the present application, the perovskite luminophore may be any perovskite quantum dot coated by a template in the prior art, and the pores of the template have not collapsed or have not completely collapsed, so as to retain the pores as the post-processing mass transfer path. At the same time, it should be pointed out that the essence of this application is a technology for post-processing a substance (i.e., a perovskite luminophore) that has synthesized perovskite quantum dots in a template. For the preparation method of the perovskite luminophore, please refer to a perovskite nanocrystalline fluorescent material and its preparation method and application (publication number: CN118165723A) previously applied for and disclosed by our company, or other related methods disclosed in the prior art. At the same time, the present invention also provides the following methods as examples:

[0012] A method for preparing a perovskite luminescent body comprises the following steps:

[0013] Step 1: Grind and mix perovskite precursors such as cesium halide and lead halide and a template agent to obtain a mixture.

[0014] Step 2: Heat the mixture to allow the precursors to react in the template to form a perovskite emitter.

[0015] The above methods are merely examples and do not constitute a limitation on the method for preparing perovskite light emitters.

[0016] Furthermore, the stearate includes at least one of calcium stearate, zinc stearate, magnesium stearate, and barium stearate. At room temperature, the hardness of stearate powder is relatively low and the texture is relatively soft. Therefore, the stearate powder is easily squeezed and deformed under the action of external force.

[0017] Furthermore, the perovskite quantum dots are of ABX3 structure;

[0018] Wherein, the A position is at least one of Cs, Rb, FA, MA, and GA;

[0019] The B position is at least one of Pb, Sn, and Cu;

[0020] X is one or both of Cl, Br or I.

[0021] Furthermore, one end of the stearate is deformed under the action of external force and then partially embedded in the pores of the template to serve as a pore-blocking agent, and the other end of the stearate is exposed outside the template to serve as a lubricant.

[0022] On the one hand, the present invention utilizes the easy deformation of stearate under the action of external force to achieve the purpose of plugging holes, and on the other hand, it utilizes the grafting of a number of stearate powders in the pores of the template to achieve the lubrication effect during the subsequent melt processing of perovskite quantum dots. At this time, stearate and perovskite quantum dots move synchronously as a whole during the subsequent melt extrusion process. As is well known, stearate is usually used as a lubricant, release agent, etc. in plastic products (including resin products) to reduce the viscosity of the plastic melt and improve its fluidity and processability. This makes the plastic smoother during extrusion molding (such as quantum dot films, quantum dot diffusion plates, light conversion films, etc.), reduces resistance and friction during processing, thereby improving production efficiency and product quality.

[0023] Furthermore, the deformation of the stearate under the action of external force comes from the external extrusion, impact or friction provided in the grinding stage;

[0024] The grinding includes at least one of ball milling, manual grinding and mechanical grinding.

[0025] Furthermore, the template is a microporous material and / or a mesoporous material;

[0026] The microporous material is one of microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride;

[0027] The mesoporous material is one of mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.

[0028] Furthermore, the particle size of the stearate powder>the pore size of the template>the size of the organic ligand molecule. Under the guidance of the technical concept of the present invention, technicians in this field can flexibly adjust the particle size of the stearate powder, the pore size of the template pore and the size of the organic ligand molecule. By accurately controlling the sizes of these three, the objectives of the present invention can be achieved. All selections of the three specific substances and adjustments of the sizes based on the above technical concept should be included in the protection scope of the present invention.

[0029] Further, the organic ligand includes at least one of oleic acid, oleylamine, ethanolamine, butylamine, and trimethoxypropylamine. As generally understood by those skilled in the art, any organic ligand with a molecular size smaller than the pore size of the template agent can be applied to the present invention, and is not limited to the examples listed above.

[0030] A method for preparing solid-liquid hybrid encapsulated perovskite quantum dots comprises the following steps:

[0031] S1. Mixing a perovskite luminescent body and an organic ligand and performing an immersion stirring treatment to obtain a mixture; the perovskite luminescent body includes a template and perovskite quantum dots located in the pores of the template, and the template has pores for the mass transfer path of the organic ligand;

[0032] S2, blending the mixture with stearate, and placing the mixture in a grinding device for grinding.

[0033] It should be pointed out that the perovskite light-emitting system of the present invention refers to perovskite quantum dots with a template.

[0034] Furthermore, the grinding speed in step S2 is at least 200 r / min, and the grinding time is at least 10 min.

[0035] An application of perovskite quantum dots, wherein the perovskite quantum dots can be applied to perovskite diffuser plates, inkjet printing, wavelength conversion films, quantum dot films or Micro LEDs.

[0036] The beneficial effects of the present invention are mainly reflected in:

[0037] (1) The post-processing technology of the present application is targeted at: Perovskite quantum dots that have been synthesized (or, Perovskite quantum dots with a template). Moreover, the prepared quantum dot material has the advantages of high repeatability and high luminescence efficiency. In the post-processing stage, the organic ligand of the present invention interacts with the Pb2+ of the perovskite quantum dots by immersion and diffusion into the pores of the template, thereby passivating the surface defects of the perovskite quantum dots. In addition, calcium stearate used in the solid-state encapsulation stage can form a coating on the outside of the perovskite quantum dots to isolate them from water and oxygen to prevent the degradation of the perovskite quantum dots.

[0038] (2) The present invention enables stearate to have both a pore-blocking effect (for the template pores) and a lubricating effect (for the periphery of the template) in the system, so as to improve the processability of the perovskite quantum dot material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The spectrum of the sample obtained in Example 1 of the present invention;

[0040] Figure 2 The spectrum of the sample obtained for Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] Embodiment 1:

[0043] This embodiment provides a method for preparing solid-liquid hybrid encapsulated perovskite quantum dots, comprising the following steps:

[0044] Step 1: Grind and mix 233 mg of cesium bromide, 367 mg of lead bromide and 600 mg of template MCM-41 for 2 hours at a ball mill speed of 240 r / min to obtain the corresponding CsPbBr3 solid phase precursor (mixed powder). The mixed powder is heated to 530 degrees Celsius in an air atmosphere and maintained for 60 minutes; cool and crystallize to react in the pores of MCM-41 and form CsPbBr3 perovskite quantum dots.

[0045] Step 2: Pour the product obtained in step 1 and 5 mL of ethanolamine into a bottle, soak and stir, so that the organic small molecule ligand enters the pores of MCM-41 and coordinates with the Pb on the surface of the quantum dots.

[0046] Step 3: 1.2 g of calcium stearate is blended with the product obtained in step 2 and wet-grinded at a grinding speed of at least 200 r / min for at least 10 min. After grinding, the mixture is dried in an oven at 60°C.

[0047] In the above, the particle size of the stearate powder>the pore size of the template>the size of the organic ligand molecule.

[0048] Experimental analysis: The powder after the above treatment was tested for fluorescence quantum yield (PLQY), as shown in Table 1, and the PLQY of the sample was 91%. In comparison, the PLQY of the unencapsulated perovskite quantum dots provided in Comparative Example 1 was 52%, the PLQY of the perovskite quantum dots only encapsulated in liquid state provided in Comparative Example 2 was 89%, and the PLQY of the perovskite quantum dots only encapsulated in solid state provided in Comparative Example 3 was 53%. The improvement of PLQY indicates that liquid encapsulation can passivate the defects of CsPbBr3 perovskite quantum dots, and solid-state encapsulation alone cannot improve PLQY.

[0049] The stability of the powder after the above treatment was tested under strong blue light irradiation environment. See Table 1 for details. 2 After continuous irradiation of blue light (450nm) for 100 hours, the luminous intensity of the perovskite quantum dots can maintain 88% of the original intensity. In comparison, the luminous intensity of the unencapsulated perovskite quantum dots provided in Comparative Example 1 dropped to 32% of the initial intensity after 100 hours under the same blue light test conditions, the luminous intensity of the perovskite quantum dots provided in Comparative Example 2 dropped to 67% of the initial intensity after 100 hours under the same blue light test conditions, and the luminous intensity of the perovskite quantum dots provided in Comparative Example 3 dropped to 78% of the initial intensity after 100 hours under the same blue light test conditions. The blue light stability test proves that solid-phase encapsulation significantly improves the photostability of CsPbBr3 quantum dots.

[0050] The comprehensive fluorescence quantum yield and blue light stability test data prove that solid-liquid hybrid encapsulation will improve PLQY and photostability at the same time.

[0051] Embodiment 2:

[0052] The difference from Example 1 is that the calcium stearate in step S3 is replaced by magnesium stearate.

[0053] Embodiment 3:

[0054] The difference from Example 1 is that the calcium stearate in step S3 is replaced by zinc stearate.

[0055] Embodiment 4:

[0056] The difference from Example 1 is that the calcium stearate in step S3 is replaced by barium stearate.

[0057] Comparative Example 1:

[0058] The difference from Example 1 is that no packaging is performed.

[0059] Step 1: Grind and mix 233 mg of cesium bromide, 367 mg of lead bromide and 600 mg of template MCM-41 for 2 hours at a ball mill speed of 240 r / min to obtain the corresponding CsPbBr3 solid phase precursor. The mixed powder is heated to 530 degrees Celsius in an air atmosphere and maintained for 60 minutes; the mixture is cooled and crystallized to react in the pores of MCM-41 and form perovskite quantum dots.

[0060] Comparative Example 2:

[0061] The difference from Example 1 is that only liquid packaging is performed.

[0062] Step 1: Grind and mix 233 mg of cesium bromide, 367 mg of lead bromide and 600 mg of template MCM-41 for 2 hours at a ball mill speed of 240 r / min to obtain the corresponding CsPbBr3 solid phase precursor. The mixed powder is heated to 530 degrees Celsius in an air atmosphere and maintained for 60 minutes; the mixture is cooled and crystallized to react in the pores of MCM-41 and form perovskite quantum dots.

[0063] Step 2: Pour the product obtained in step 1 and 5 mL of ethanolamine into a bottle, soak and stir, so that the organic small molecule ligand enters the pores of MCM-41 and coordinates with the Pb on the surface of the quantum dots.

[0064] Comparative Example 3:

[0065] The difference from the first embodiment is that only solid-state packaging is performed.

[0066] Step 1: Grind and mix 233 mg of cesium bromide, 367 mg of lead bromide and 600 mg of template MCM-41 for 2 hours at a ball mill speed of 240 r / min to obtain the corresponding CsPbBr3 solid phase precursor. The mixed powder is heated to 530 degrees Celsius in an air atmosphere and maintained for 60 minutes; the mixture is cooled and crystallized to react in the pores of MCM-41 and form perovskite quantum dots.

[0067] Step 2: 1.2 g of calcium stearate is blended with the product obtained in step 1 and wet-grinded at a grinding speed of at least 200 r / min for at least 10 min. After grinding, the mixture is dried in an oven at 60°C.

[0068] Comparing Example 1 with Comparative Examples 1-3, it can be explained that only a single encapsulation method cannot solve both PLQY and photostability at the same time, and only a solid-liquid hybrid encapsulation method can greatly improve the PLQY and photostability of perovskite.

[0069] The final products were prepared from the above examples. The PLQY and photostability of the products under 450nm blue laser are shown in Table 1.

[0070] Table 1: Comparison of PLQY and stability test results of samples from different embodiments (comparative examples)

[0071]

[0072] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A solid-liquid hybrid encapsulated perovskite quantum dot, characterized in that: It comprises a template having pores, wherein the pores of the template are provided with perovskite quantum dots and organic ligands, and the organic ligands are used to passivate the surface defects of the perovskite quantum dots; Also included is a stearate, which is deformed under the action of an external force and then partially embedded in the pores of the template to block the pores; The particle size of the stearate powder>the pore size of the template>the size of the organic ligand molecule.

2. The solid-liquid hybrid encapsulated perovskite quantum dots according to claim 1, characterized in that: The perovskite quantum dots are of ABX3 structure; Wherein, the A position is at least one of Cs, Rb, FA, MA, and GA; The B site is at least one of Pb, Sn, and Cu; X is one or both of Cl, Br or I.

3. The solid-liquid hybrid encapsulated perovskite quantum dots according to claim 1, characterized in that: One end of the stearate is deformed under the action of external force and then partially embedded in the pores of the template to serve as a pore blocking agent, and the other end of the stearate is exposed outside the template to serve as a lubricant.

4. The solid-liquid hybrid encapsulated perovskite quantum dots according to claim 3, characterized in that: The deformation of the stearate under the action of external force comes from the external extrusion, impact or friction provided in the grinding stage; The grinding includes at least one of ball milling, manual grinding and mechanical grinding.

5. The solid-liquid hybrid encapsulated perovskite quantum dots according to claim 1, characterized in that: The template is a microporous material and / or a mesoporous material; The microporous material is one of microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride; The mesoporous material is one of mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.

6. The solid-liquid hybrid encapsulated perovskite quantum dots according to claim 3, characterized in that: The stearate includes at least one of calcium stearate, zinc stearate, magnesium stearate and barium stearate.

7. The solid-liquid hybrid encapsulated perovskite quantum dots according to claim 1, characterized in that: The organic ligand includes at least one of oleic acid, oleylamine, ethanolamine, butylamine and trimethoxypropylamine.

8. The method for preparing solid-liquid hybrid encapsulated perovskite quantum dots according to any one of claims 1 to 7, characterized in that: The steps include: S1. Mixing a perovskite luminescent body and an organic ligand and performing an immersion stirring treatment to obtain a mixture; the perovskite luminescent body includes a template and perovskite quantum dots located in the pores of the template, and the template has pores for the mass transfer path of the organic ligand; S2, blending the mixture with stearate, and placing the mixture in a grinding device for grinding.

9. The method for preparing solid-liquid hybrid encapsulated perovskite quantum dots according to claim 8, characterized in that: The grinding speed in step S2 is at least 200 r / min, and the grinding time is at least 10 min.

10. The use of a perovskite quantum dot according to any one of claims 1 to 7, characterized in that: The perovskite quantum dots can be applied in perovskite diffuser plates, inkjet printing, wavelength conversion films, quantum dot films or Micro LEDs.

Citation Information

Patent Citations

  • Perovskite nanocrystalline fluorescent material and preparation method and application thereof

    CN118165723A

  • All-solid-state post-processing technology of perovskite quantum dots and application of all-solid-state post-processing technology

    CN118978913A

  • Perovskite quantum dot, preparation method thereof and quantum dot device

    CN114316969A

  • Post-treatment method for rapidly improving stability of all-inorganic perovskite quantum dots

    CN115746830A

  • Quantum dot composite material and manufacturing method and application thereof

    US20170153382A1